The growing season of broccoli in the southern region of Dagestan - E. G. Gadjimustapaeva (Труды по прикладной ботанике, генетике и селекции)
Background. Broccoli has valuable chemical composition, is a source of mineral elements, ascorbic acid, a significant amount of nitrogenous and biologically active substances, and has medicinal properties. For the year-round cultivation of this valuable crop in Dagestan, it is required to develop a conveyor of varieties and hybrids of different ripening groups, and determine the timing of planting seeds and transplanting seedlings.Materials and methods. Fourteen varieties and hybrids of broccoli from the global collection of VIR were studied in comparison with the 'Tonus' reference variety. Research was carried out at Dagestan Experiment Station of VIR in 2015-2017 in the summer/autumn season of crop cultivation. Seeds for seedlings were sown in open ground in the second 10-day period of June; shoots were obtained on June 23-24. Transplanting of the seedlings was carried out in the third 10-day period of July. The planting scheme was 70x40 cm; the plot area for one accession was 8.4 m2. Agricultural practice used for cultivation is generally accepted for cabbage family crops in the region.Results and conclusions. In the summer/autumn season of cultivation, it is possible to harvest high-quality broccoli crop in Derbent District. During the study, the length of the growing season for the accessions and the quality of the harvest were determined, taking into account the effect of temperature factors in the year of study. Optimal doses of mineral fertilizers and the best number of chemical treatments against pests were identified. To obtain a marketable head in broccoli, the main limiting factors are the temperature and humidity of soil and air. The longer the temperature stays within the range from 15 to 20°C during the growth period in the first phase after planting before the start of head formation, the higher is the yield. The longer the temperature remains above 25°C during the period from the beginning of head formation to the accession's full commercial fitness, the lower is the quality of the marketable head. The longer are the periods with temperatures between 15 and 20°C during the first growth phase and with temperatures between 10 and 15°C during the formation of the head, the lower is the percentage of broccoli heads with a rough uneven surface. The temperature above 20°C in the second phase was conducive to the formation of loose heads with emergence of flowers. Uniform formation of marketable heads was observed in the reference variety 'Tonus': 10% of central heads were formed on the 82nd day, and 100% on the 90th, that is within only eight days. Early-ripening broccoli varieties showed poor head quality: large buds, uneven surface, and rapid divarication of heads. Experimental data on the cultivation of marketable broccoli heads may be recommended to farmers and amateur vegetable growers.